2021
DOI: 10.3390/app11031326
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Post-Flowering Climate Conditions on Anthocyanin Profile of Strawberry Cultivars Grown from North to South Europe

Abstract: The effect of cultivar and environmental variations and their interaction on anthocyanin components of strawberry were assessed for six cultivars grown in five locations from North to South of Europe in two different years. To evaluate the impact of latitude- and altitude-related factors, daily mean (Tmean), maximum (Tmax) and minimum (Tmin) temperature and global radiation accumulated for 3, 5, 10 and 15 days before fruit sampling, was analyzed. In general, fruits grown in the south were more enriched in tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
(79 reference statements)
1
8
2
Order By: Relevance
“…As for wild strawberry 'Regina', we found a significantly higher content of anthocyanins (0.337 mg•g −1 ) than in 'Baron von Solemacher', which proves a significant influence of the genotype. This is also confirmed by Krüger et al [53], who found that the total anthocyanin concentration in strawberry is both qualitatively and quantitatively known to be strongly influenced by the genotype and, likewise, by external factors such as temperature and light (photoperiod, quantity, and wavelength including UV-light).…”
Section: Biochemical Analysis Of Leaves and Fruitssupporting
confidence: 79%
“…As for wild strawberry 'Regina', we found a significantly higher content of anthocyanins (0.337 mg•g −1 ) than in 'Baron von Solemacher', which proves a significant influence of the genotype. This is also confirmed by Krüger et al [53], who found that the total anthocyanin concentration in strawberry is both qualitatively and quantitatively known to be strongly influenced by the genotype and, likewise, by external factors such as temperature and light (photoperiod, quantity, and wavelength including UV-light).…”
Section: Biochemical Analysis Of Leaves and Fruitssupporting
confidence: 79%
“…and 1500 m.a.s.l. (A ˚kerstro ¨m et al 2010;Kru ¨ger et al 2021). It is currently known that the total anthocyanin contents in strawberries are strongly influenced, both qualitatively and quantitatively, by external factors such as high or low temperatures and light (photoperiod, quantity, and wavelength including UV-light), and in turn these factors influence the altitude at which the fruits are grown (Kru ¨ger et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Lower latitudes within Europe have also shown to favor anthocyanin accumulation in strawberries and currants ( Ribes sp.) compared to higher ones, with significant differences in pigment pattern between southern and northern samples [ 58 , 59 , 60 , 61 , 62 ]. However, total phenols and strawberry fruit antioxidant capacity were generally increased in higher latitudes, which may be partially explained by higher ascorbic acid and tannins; curiously, our data showed a trend of increased TEAC values (mean TEAC value of 25.88 mmol/Trolox in Norway, compared to 23.8 and 23.19 mmol/Trolox in Germany and Poland, respectively) in the Norwegian samples, except for ‘Veten’.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary metabolite analysis by HPLC coupled to ion trap mass spectrophotometer (anthocyanins) and RP-HPLC/UV (colorless polyphenols) was carried out as described in [ 59 ]. Volatile analysis by HS-SPME/GC-MS was executed following the protocol presented by Pott et al [ 84 ] All metabolite-relative content obtained from the three techniques was normalized to dry weight.…”
Section: Methodsmentioning
confidence: 99%